2023
DOI: 10.1029/2022ja031037
|View full text |Cite
|
Sign up to set email alerts
|

On the Variation of Column Density Ratio ΣO/N2 in the Upper Atmosphere Using Principal Component Analysis in 2‐Dimensional Images

Abstract: The variability of the thermosphere on a daily basis is influenced by a variety of factors, including solar, geomagnetic, and meteorological drivers. The column density ratio of atomic oxygen to molecular nitrogen (ΣO/N2) is a useful parameter for quantifying this variability, and has been shown to closely correspond to F‐region electron density, total electron content, and upper atmospheric transport. Despite the significance of the ΣO/N2, the relative contributions of these drivers to thermospheric variabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…One of the key state parameters that ICON measures is wind profiles spanning 90-300 km at low and middle latitudes (Englert et al, 2023;Harding et al, 2021;Makela et al, 2021), and GOLD provides unparalleled synoptic observations of disk O/N 2 and temperatures (Eastes et al, 2020). The two missions have been revolutionizing the understanding of the ionosphere-thermosphere dynamics during solar and geomagnetically active and quiet times (e.g., Cai et al, 2023;Eastes et al, 2020;England et al, 2020;Gan et al, 2020aGan et al, , 2020bGan et al, , 2023aGan et al, , 2023bGoel et al, 2023;Immel et al, 2023;Laskar et al, 2022;McGinness et al, 2023;Oberheide et al, 2020). The current investigation is motivated by a previous study- Gan et al (2020a)-that reported the first observational changes in atomic oxygen (OI 135.6 nm brightness was used as a proxy) from the GOLD mission during the 5 November 2018 CME (Coronal Mass Ejection) storm.…”
Section: Citationmentioning
confidence: 99%
“…One of the key state parameters that ICON measures is wind profiles spanning 90-300 km at low and middle latitudes (Englert et al, 2023;Harding et al, 2021;Makela et al, 2021), and GOLD provides unparalleled synoptic observations of disk O/N 2 and temperatures (Eastes et al, 2020). The two missions have been revolutionizing the understanding of the ionosphere-thermosphere dynamics during solar and geomagnetically active and quiet times (e.g., Cai et al, 2023;Eastes et al, 2020;England et al, 2020;Gan et al, 2020aGan et al, , 2020bGan et al, , 2023aGan et al, , 2023bGoel et al, 2023;Immel et al, 2023;Laskar et al, 2022;McGinness et al, 2023;Oberheide et al, 2020). The current investigation is motivated by a previous study- Gan et al (2020a)-that reported the first observational changes in atomic oxygen (OI 135.6 nm brightness was used as a proxy) from the GOLD mission during the 5 November 2018 CME (Coronal Mass Ejection) storm.…”
Section: Citationmentioning
confidence: 99%